A new therapeutic pathway in autoimmune diseases: chimeric antigen receptor T cells (CAR-T) targeting specific cell subtypes or antigen-specific B lymphocytes—a brief review - María Fernanda Segovia; Diana Landoni; Yohana Defranchi; Rodrigo Calderón Jofré; Carlos A. Flores Olivares; Gerson D. Keppeke (Exploration of Immunology)
In hematological malignancies, autologous immunotherapy with T lymphocytes expressing a chimeric antigen receptor (CAR-T) has been successfully applied. CAR enhances the immuno-cellular effector system directly against cells expressing target antigens. The objective here was to discuss the prospects of applying CAR-T and its variants in autoimmune diseases (AIDs) to deplete pathogenic autoantibodies by eliminating B lymphocytes and plasma cells. B cells play a crucial role in the pathogenesis of AID through the production of autoantibodies, cytokine dysregulation, antigen presentation, and regulatory dysfunction. In AID with numerous autoreactive clones against various autoantigens, such as systemic lupus erythematosus, rheumatoid arthritis, vasculitis, myositis, and systemic sclerosis, CAR-T targeting CD19/CD20 and B-cell maturation antigen (BCMA) have shown success in preclinical and clinical studies, representing an innovative option for refractory patients when standard treatments fail. The suppression of B lymphocytes reactive against specific antigens using cytolytic T cells carrying a chimeric autoantibody receptor (CAAR-T) offers a promising approach for managing various AIDs, especially those with characterized pathogenic autoantibodies, such as pemphigus vulgaris, myasthenia gravis, and anti-NMDAR autoimmune encephalitis. CAAR-T allows the elimination of autoreactive B lymphocytes without compromising the general functionality of the immune system, minimizing common side effects in general immunosuppressive therapies, including immunobiologicals and CAR-T. In vitro, preclinical, and clinical (phase 1) studies have demonstrated the efficacy and specificity of CAR-T and CAAR-T in several AIDs; however, extensive clinical trials (phase 3) are required to assess their safety and clinical applicability. These advances promise to enhance precision medicine in the management of AIDs, offering personalized treatments for individual patients.